2023
DOI: 10.1186/s12974-023-02827-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social defeat alters brain vascular-associated cell gene expression patterns leading to vascular dysfunction and immune system activation

Abstract: Brain vascular integrity is critical for brain health, and its disruption is implicated in many brain pathologies, including psychiatric disorders. Brain-vascular barriers are a complex cellular landscape composed of endothelial, glial, mural, and immune cells. Yet currently, little is known about these brain vascular-associated cells (BVACs) in health and disease. Previously, we demonstrated that 14 days of chronic social defeat (CSD), a mouse paradigm that produces anxiety and depressive-like behaviors, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Although disruption of the NVU has been associated with chronic stress, the exact effects remain disputed. Some studies in the literature suggest that chronic stress leads to BBB dysfunction [24][25][26][27][28][29][30][31][32]. For example, one study reported scattered deposition of plasma immunoglobulins and erythrocytes in the brain following exposure to chronic social defeat stress, indicating the occurrence of cerebrovascular microhemorrhages [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although disruption of the NVU has been associated with chronic stress, the exact effects remain disputed. Some studies in the literature suggest that chronic stress leads to BBB dysfunction [24][25][26][27][28][29][30][31][32]. For example, one study reported scattered deposition of plasma immunoglobulins and erythrocytes in the brain following exposure to chronic social defeat stress, indicating the occurrence of cerebrovascular microhemorrhages [28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, both clinical and preclinical studies have suggested that the disruption of the NVU may serve as a potential neuropathological link between chronic stress and depression [24][25][26][27][28][29][30][31][32]. For instance, studies in the model of chronic social defeat stress (CSDS) have shown a decrease in the expression of Claudin-5 (Cldn5) in the nucleus accumbens (Nac).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This included decreased levels of S100b (F (1,25) =22.56, p<0.0001) and Aqp4 transcripts (F (1,25) =7.960, p=0.009). Virally mediated knockdown of Aqp4 also reduced expression levels of S100b and Aqp4, alongside Megf10 (F(1,25) =6.647, p=0.016) and Vegf (F(1,25) =6.311, p=0.019) in the frontal cortex. Together, these data indicate that transcripts reflecting the phenotype of astrocytes shift prior to the emergence of stress-induced deficits in behavior, and that depletion of Aqp4 in PFC astrocytes is sufficient to disrupt markers of astrocyte identity (i.e., S100b) and function (i.e., Megf10, Vegf).AQP4 knockdown in the PFC and sub-CUS induce astrocyte dystrophyA separate cohort of mice received intravascular injections of tomato lectin prior to perfusion and immunostaining (d8), with subsequent analyses focused on astrocyte-blood vessel interaction in the PFC (Fig 5A).…”
mentioning
confidence: 93%
“…Alongside pronounced astrocyte dystrophy, recent studies indicate disruption of the neurovasculature in stress. This includes loss of tight junction proteins, reduced cerebral blood flow, and heightened blood-brain barrier (BBB) permeability in select brain regions [9,[23][24][25][26][27][28]. Together, these findings suggest that stressinduced dysregulation of astrocytes at the PFC neurovascular interface leads to behavioral and cognitive consequences.…”
Section: Introductionmentioning
confidence: 99%